AB0079 Independent Validation of 14-3-3ETA Assay Reproducibility, Consistent with Omeract Soluble Biomarker Criteria. (9th June 2015) - Hughes, N.; Boss, S.; Longe, R.; Sohal, P.; Jimenez, C.; Maksymowych, W.P.; Marotta, A.
Abstract : Background: 14-3-3η is a diagnostic biomarker involved in the joint damage process and is complementary to RF and anti-CCP for the diagnosis of early and established RA. The OMERACT soluble biomarker sub-committee has published validation criteria related to truth, discrimination and feasibility for biomarkers reflecting structural damage. Most RA biomarker assays have not undergone validation along key OMERACT performance criteria prior to clinical validation studies. 1 We have reported that the 14-3-3η biomarker is highly stable and is not confounded by age, gender or menopausal status 2, that 14-3-3η values reported in the United States using the Quest laboratory developed test are substantially equivalent to those using the Augurex CE marked/Health Canada approved 14-3-3η IVD and that RF does not impact the quantification of 14-3-3η. 3 Objectives: To validate the reproducibility of the Augurex 14-3-3η ELISA testing method when transferred to an automated platform in a major Canadian lab services company, to support routine operation in a high volume clinical testing environment. Methods: The Health Canada approved 14-3-3η ELISA relies on a manual testing method with a calibrator range of 0.16 to 20 ng/mL. Accuracy, intra and inter-assay variation were assessed using 5 serum samples with 14-3-3η concentrations ranging from negative to above the upper limits of the assay. To assess accuracy, recoveries were measured using 5 replicates and compared to pre-determined 14-3-3η values. Intra-day precision was determined with 20 replicates while inter-day precision was performed over 6 days with 5 replicates. Method linearity was conducted using 5 serially diluted samples within analytical measureable range (AMR). The cut-off for the normal population was performed in 147 presumed healthy individuals, setting the cut-off at the 90th percentile. For equivalency testing, the automated and manual method were compared, each at different sites by testing 121 rheumatoid arthritis samples for 14-3-3η. Spearman correlations were performed to assess the relationship between 14-3-3η titres at both sites. Results: Results of accuracy, intra and inter-assay testing were all within pre-specified parameters. Mean accuracy was 111% with a range of 104%>119%. Intra-and inter-day precision were all within the 20% target. Linearity recoveries was highly correlated delivering a R2 >0.99 and a mean accuracy of 86% from 0.20-16.3 ng/mL. Testing of the 147 presumed healthy individuals confirms the manufacturer's positivity cut-off of >0.19ng/ml. Mean 14-3-3η values generated at the two sites were compared and yielded a 90% qualitative concordance. Of the 58 samples within the AMR, the Spearman correlation revealed a statistically significant correlation of r=0.97, p<0.0001 between the two sets of results. Conclusions: The 14-3-3η ELISA demonstrates strong reproducibility and clinical performance when transitioned to an automated high-volume testing platform, consistent with essential OMERACT soluble biomarker validation criteria. References: J Rheumatol. 2009 Aug;36(8):1785 and 1792. Arthritis Rheum. 2012. 64Suppl 10:2118. Ann Rheum Dis. 2014;73:111. Disclosure of Interest: N. Hughes Employee of: LifeLabs Medical Laboratory Services, S. Boss Employee of: LifeLabs Medical Laboratory Services, R. Longe Employee of: LifeLabs Medical Laboratory Services, P. Sohal Employee of: LifeLabs Medical Laboratory Services, C. Jimenez Employee of: LifeLabs Medical Laboratory Services, W. Maksymowych Consultant for: Augurex Life Sciences Corp, (Co-inventor of 14-3-3η), A. Marotta Employee of: Augurex Life Sciences, (Co-inventor of 14-3-3η)